A Palette of Minimally Tagged Sucrose Analogues for Real‐Time Raman Imaging of Intracellular Plant Metabolism. (26th February 2021) - de Moliner, Fabio; Knox, Kirsten; Gordon, Doireann; Lee, Martin; Tipping, William J.; Geddis, Ailsa; Reinders, Anke; Ward, John M.; Oparka, Karl; Vendrell, Marc
Abstract: Sucrose is the main saccharide used for long‐distance transport in plants and plays an essential role in energy metabolism; however, there are no analogues for real‐time imaging in live cells. We have optimised a synthetic approach to prepare sucrose analogues including very small (≈50 Da or less) Raman tags in the fructose moiety. Spectroscopic analysis identified the alkyne‐tagged compound 6 as a sucrose analogue recognised by endogenous transporters in live cells and with higher Raman intensity than other sucrose derivatives. Herein, we demonstrate the application of compound 6 as the first optical probe to visualise real‐time uptake and intracellular localisation of sucrose in live plant cells using Raman microscopy. Abstract : We describe a chemical strategy to prepare sucrose derivatives with vibrational tags and the characterisation of the first optical analogue of sucrose able to image real‐time trafficking of sucrose in live plant cells.